The Stringent Response of Salmonella Typhimurium - Chau, Nhu Y Elizabeth (My University, 2021)
Bacteria inhabit diverse environmental niches and consequently, must modulate their metabolism to adapt to stress. The nucleotide second messengers guanosine tetraphosphate (ppGpp) and guanosine pentaphosphate (pppGpp) (collectively referred to as (p)ppGpp) are essential for survival during nutrient starvation. (p)ppGpp is synthesized by the RelA-SpoT homologue (RSH) protein family and coordinates the control of cellular metabolism through its combined effect on over 50 proteins. While the role of (p)ppGpp has largely been associated with nutrient limitation, recent studies have shown that (p)ppGpp and related nucleotides have a previously underappreciated effect on different aspects of bacterial physiology, such as regulating bacterial interactions with its host. This thesis focuses on the coordination of virulence gene expression and evasion of host immunity by (p)ppGpp in Salmonella enterica serovar Typhimurium. In the first data chapter, I describe the role of (p)ppGpp in mediating bacterial resistance to killing by the human complement system. I identified that (p)ppGpp activates ppnN, a nucleotide metabolism associated enzyme, and the biosynthesis of lipopolysaccharide O-antigen to protect Salmonella from cell lysis by complement. The second data chapter compares and contrasts the stringent response of an invasive clinical isolate of Salmonella Typhimurium to a strain of Salmonella Typhimurium that causes acute gastroenteritis using RNA-sequencing. Critical analysis of our transcriptomics dataset showed that flagellar-based motility is differentially regulated by (p)ppGpp in the two strains of Salmonella. Together, these findings demonstrate that (p)ppGpp has significant functional roles beyond mediating adaptation to nutrient limitation.
Keywords: Salmonella Typhimurium, stringent response, host-pathogen interactions, innate immunity